2003
DOI: 10.1002/app.12091
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and thermomechanical properties of biocomposites made from modified recycled cellulose and recycled polypropylene

Abstract: ABSTRACT:Residual cellulose fibers from the paper industry have been used as reinforcements in recycled polypropylene (PP) composites. The main obstacle to obtaining good properties with this biocomposite is deficiencies in the compatibility between the nonpolar matrices and the polar cellulose fibers used as reinforcements. The aim of this work was to improve the compatibilization between these cellulose fibers and the PP matrix with four different methods: modification by the addition of polypropylene-maleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…An increased thermal stability was found in PP composites with GMA modified hemp; moreover, marked changes in the morphology and overall crystallization rate of PP were observed in these composites due to the enhanced nucleating effect on the fiber surface. For all examined materials, the mechanical analysis showed that tensile modulus and elongation at break are significantly affected by the type and amount of fiber (aspect ratio: [10][11][12][13][14][15][16][17][18][19][20], as are affected by the structure (and concentration) of compatibilizer. In particular, the addition of functionalized polyolefins (PP-g-GMA, PS-co-MA) resulted in an increased stiffness owing to the improved fiber-matrix adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased thermal stability was found in PP composites with GMA modified hemp; moreover, marked changes in the morphology and overall crystallization rate of PP were observed in these composites due to the enhanced nucleating effect on the fiber surface. For all examined materials, the mechanical analysis showed that tensile modulus and elongation at break are significantly affected by the type and amount of fiber (aspect ratio: [10][11][12][13][14][15][16][17][18][19][20], as are affected by the structure (and concentration) of compatibilizer. In particular, the addition of functionalized polyolefins (PP-g-GMA, PS-co-MA) resulted in an increased stiffness owing to the improved fiber-matrix adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer modification appears to be a quick, effective method to provide good interfacial adhesion, in contrast to fiber modification, which generally involves solvent based processes. Maleated PP (PP-g-MA) have been extensively used as compatibilizers in various polyolefin composites with natural fibers [12][13][14]; glycidyl methacrylate grafted PP (PP-g-GMA) has been employed in composites of PP with hemp fibers [15].…”
mentioning
confidence: 99%
“…The improvement of Young`s modulus may be due to the high disaggregation of fibers with elevated elastic modulus. Meanwhile soaking the composite in oil for 24 h did not show any notable effect on the composite elasticity [33,34] as in Fig. 5a.…”
Section: Effect Of Chemical Treatment On the Composites` Mechanical Pmentioning
confidence: 84%
“…(4a, b). On the other side, fiber-reinforced HIPS composites had relatively higher Young's modulus compared to HIPS alone [33]. Since the natural fibers have higher Young's modulus than the thermoplastic polymers.…”
Section: Effect Of Water Soaking On the Composites` Mechanical Propermentioning
confidence: 95%
See 1 more Smart Citation